1999
DOI: 10.1021/bp990002r
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Lead, Cadmium, and Zinc by Citrobacter Strain MCM B-181: Characterization Studies

Abstract: The biosorption process for removal of lead, cadmium, and zinc by Citrobacter strain MCM B-181, a laboratory isolate, was characterized. Effects of environmental factors and growth conditions on metal uptake capacity were studied. Pretreatment of biomass with chemical agents increased cadmium sorption efficiency; however, there was no significant enhancement in lead and zinc sorption capacity. Metal sorption by Citrobacter strain MCM B-181 was found to be influenced by the pH of the solution, initial metal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(113 citation statements)
references
References 30 publications
10
97
2
4
Order By: Relevance
“…These results showed that both Alternaria alternata and Penicillium aurantiogriseum are suitable for using as cadmium and mercury accumulators in wastewater. Similar results with respect to biosorption of cadmium and other heavy metals by fungi and bacteria have been reported earlier (Chang et al, 1997;Puranik and Paknikar, 1999;Costa et al, 2001;Pardo et al, 2003;Kefala et al, 1999;Ghoslan et al, 1999;Say et al, 2001;Watanabe et al, 2003;Ozdemir et al, 2004;Ayangbenro, and Babalola, 2017). Kumar et al, (2014) 2.55 mg/g of Cr respectively.…”
Section: Heavy Metals Concentrationssupporting
confidence: 88%
“…These results showed that both Alternaria alternata and Penicillium aurantiogriseum are suitable for using as cadmium and mercury accumulators in wastewater. Similar results with respect to biosorption of cadmium and other heavy metals by fungi and bacteria have been reported earlier (Chang et al, 1997;Puranik and Paknikar, 1999;Costa et al, 2001;Pardo et al, 2003;Kefala et al, 1999;Ghoslan et al, 1999;Say et al, 2001;Watanabe et al, 2003;Ozdemir et al, 2004;Ayangbenro, and Babalola, 2017). Kumar et al, (2014) 2.55 mg/g of Cr respectively.…”
Section: Heavy Metals Concentrationssupporting
confidence: 88%
“…The rate of increase of chromium removal was not proportionate to the increase in bgh biomass, ( Figure 5). This could be attributed to interference between binding sites at higher concentrations (Puranik and Paknikar, 1999).…”
Section: Biosorption Kinetics and Effect Of Biomass Quantity On Chrommentioning
confidence: 99%
“…Higher chromium sorption at lower levels of bgh biomass could be due to the higher metal to biosorbent ratio, which decreases as the biomass quantity is increased (Puranik and Paknikar, 1999).…”
Section: Biosorption Kinetics and Effect Of Biomass Quantity On Chrommentioning
confidence: 99%
“…The effect of initial pH on the copper biosorption is given in Figure 1. Little copper uptake at low pH values is an indication of competition of excess of protons for the same binding sites on the algal cell wall (Puranik and Paknikar, 1999). The copper uptake increased with increasing pH, to the maximum near pH 5.5, then decreased at higher pH value.…”
Section: Effect Of Ph On Copper Biosorptionmentioning
confidence: 99%